Correlation between Extraction Method, Phenolic Content, and Antioxidant Activity in Red Pedada Leaves (Sonneratia caseolaris L.) - Danang Raharjo; Bagas Ardiyantoro; Anastasia Cindy Jovita Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
Sonneratia caseolaris L. (red pedada) is a mangrove species rich in bioactive compounds, yet its potential remains underutilized due to suboptimal extraction methods. This study systematically evaluated four extraction techniques maceration, Soxhlet, Microwave-Assisted Extraction (MAE), and Ultrasonic-Assisted Extraction (UAE) for their efficiency in recovering phenolic compounds and antioxidants from its leaves. Using 70% ethanol, extracts were analyzed for total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity via DPPH and ABTS assays. Results demonstrated MAE's superior performance, yielding the highest TPC (145.3 mg GAE/g), TFC (89.4 mg QE/g), and strongest antioxidant activity (DPPH IC₅₀: 18.3 µg/mL; ABTS IC₅₀: 15.2 µg/mL). UAE ranked second, followed by Soxhlet and maceration. Strong correlations between TPC/TFC and antioxidant activities confirmed phenolics as primary antioxidant contributors. The enhanced performance of MAE is attributed to its efficient cell disruption through rapid internal heating and pressure buildup, facilitating complete compound release while minimizing degradation. This study conclusively identifies MAE as the optimal method for maximizing bioactive compound recovery from S. caseolaris leaves, providing a scientific basis for its application in nutraceutical and pharmaceutical industries.